Development of Three-Tier Diagnostic Test to Identify Physics Fluid Misconceptions in Class XI SMAN 2 Medan - Kezia, Ribka; Motlan (Faculty of Science and Education, UIN Walisongo Semarang, 2025)
This research aims to develop a three-tier diagnostic test instrument to identify misconceptions in fluid physics among grade XI students at SMAN 2 Medan. Misconceptions are a persistent barrier in learning physics and require specific instruments for accurate identification. The developed instrument includes multiple-choice questions (first tier), reasoning options (second tier), and confidence levels (third tier) to assess students' conceptual understanding comprehensively. Using the 4D (Define, Design, Develop, Disseminate) development model, the instrument underwent validation by experts, small-scale, and large-scale trials. The results indicated that the diagnostic test instrument is valid and reliable, effectively identifying students' misconceptions in fluid concepts such as hydrostatic pressure, Archimedes' principle, Pascal's law, and Bernoulli's principle. This instrument not only aids teachers in recognizing areas that need instructional emphasis but also contributes to improving learning strategies. The findings revealed a significant portion of students experienced misconceptions, highlighting the need for targeted pedagogical interventions. This study contributes to physics education by offering a practical diagnostic tool to improve conceptual learning and reduce misconceptions.